Modeling hidden hunger in toddlers to determine the most influential micronutrients in stunting - AISYAH, Iseu Siti; Khomsan, Ali; TANZIHA, Ikeu; RIYADI, Hadi (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: Risk factors that directly influence the incidence of stunting are the level of macronutrient and micronutrient intake. Micronutrient deficiencies cause about 1.1 million of the 3.1 million annual child deaths. This condition leads to hidden hunger, a condition of insufficient intake of micronutrients (especially iron, zinc, and iodine deficiencies). This study aimed to analyze hidden hunger in stunted and non-stunting toddlers with a multivariate model. Methods: The method used was a case-control study. A total of 71 toddlers were taken as respondents for the stunting group and 71 toddlers for the non-stunting group. The study used data collection was 2×24 hour food recall, FFQ, and blood serum collection to check zinc deficiency, iodine, hemoglobin, and urine tests. For data analysis, multivariate logistic regression and then bivariate analysis were used. Using multivariate modeling, and consideration of OR changes, the final model was obtained, including the variables of iron intake, zinc intake, iodine intake, zinc deficiency, anemia status, and hidden hunger had a significant relationship with the incidence of stunting in toddlers. Results: Toddlers with stunting were much more likely to have inadequate iron (92.95%) and zinc intake (91.54%) compared to the non-stunting group (78.87% and 77.46% respectively). A significantly higher proportion of the stunting group (40.84%) had anemia compared to the non-stunting group (5.63%). Unlike iron, zinc, and anemia, there wasn't a statistically significant relationship between iodine deficiency (p = 0.459) or hidden hunger (p = 0.058) and stunting. The results of the multivariate analysis suggest that iron intake, anemia status, and zinc deficiency are all important risk factors for stunting in toddlers. The anemia status variable was the most dominant cause of stunting because it had the highest OR value of 41.733. Conclusion: The strongest predictor was anemia status, followed by iron intake and zinc deficiency